DETERMINAN TINGKAT PENGANGGURAN ANTAR PROVINSI DI INDONESIA - Kharisma, Bayu; Wardhana, Adhitya (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.05.TAHUN.2021, 2021)
Indonesia is one of the countries with the largest unemployment in ASEAN countries. This condition is because some provinces still have unemployment rates that exceed unemployment in Indonesia. Low public education, high poverty and population in several provinces of Indonesia are among the causes of the increase in the unemployment rate in Indonesia. This research will discuss how much influence the education sector has on the average years of school ing (RLS), population, poverty rate and government spending on housing in Indonesia. The research model uses data panel regression method with a scope of 33 provinces in Indonesia. The results explain the average length of school and spending negatively affect unemployment. Then variable population numbers, the poverty rate affects positively towards unemployment.